MAKNA SIMBOLIK DAN NILAI BUDAYA RITUAL TANAM KEPALA KAMBING DALAM TRADISI HAJAT BUMI KRAMAT GANCENG: ANALISIS TEORI CLIFFORD GEERTZ - Arum Puspita (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
The goat head planting ritual is the core of the Hajat Bumi tradition, which is regularly celebrated by the community of Pondok Ranggon, Cipayung, East Jakarta. This tradition has been preserved as a manifestation of syncretism between local beliefs and Islamic religious practices, making it a contrasting object of study in an urban environment. This study aims to explore the symbolic meaning of the goat's head as a symbolic system and to understand how this ritual functions in constructing the cosmic order and collective motivation of the community. Using a qualitative-interpretive research method based on Clifford Geertz's theory of religion as a symbolic system and thick description techniques, data was collected through interviews and documentation studies. The findings show that the goat head is a dense symbol that formulates the cosmic order of sacrifice, warding off evil, and moral purification from animalistic nature. This symbol successfully creates a mood of calm and persistent motivation among residents to preserve tradition. Culturally, this ritual represents the harmonization of Islamic teachings with ancestral traditions, which ultimately affirms the unique socio-cultural identity of the Kramat Ganceng community amid modernization. This study contributes to the study of the sociology of religion through an interpretive understanding of how ritual symbols function in the cultural life of urban communities. These findings have implications for strengthening our understanding of strategies for preserving local culture in urban environments.